IMPACTS, PATTERNS, INFLUENCING FACTORS AND POLICIES OF FUELWOOD EXTRACTION IN WAY KAMBAS NATIONAL PARK, INDONESIA - Rakatama, Ari (Secretariat of Forestry Research and Development Agency, 2016)
Without good control, fuel-wood extraction from conservation forest, such as Way Kambas National Park (WKNP), can threat the existence of the forest. This paper observes the way to tackle the forest degradation in WKNP, with minimum impacts to the local people who use the fuel-wood. The study includes analysing the appropriate policy for using the fuel wood. Observation was carried out by analysing existing data and maps of WKNP in various perspectives: forest degradation, inventories, analysis of current policies, survey on how fuel-wood is extracted, mapping the mobilisation of fuel-wood gatherers, survey on fuel-wood demand, and identification of further policy options. The results show that there is fuel-wood extraction activity in WKNP influenced by income level, land ownership, the number of household members, the distance to forest area, and the age of patriarch. However, this activity is tolerated by unwritten policy at local level, although this is forbidden by written policy at national level, so this creates the failure in maintaining sustainable off-take of fuel-wood. This is supported by the fact that fuel-wood extraction in WKNP triggers the reduction of forest stock and the changes of species diversity, species evenness, and old-young tree ratio due to destructive techniques used such as slashing, scratching cambium, and cutting trees. Therefore, some recommended policy options are legalizing fuel-wood extraction with limitations, providing alternative fuel-wood and other biomass energy resources outside WKNP, running preventive and pre-emptive measures, cooperating with other stakeholders, and empowering local economic